A Comparative Study of Banking Industry Based on Appraisal System, Rewards and Employee Performance - Dr. Ishfaq Ahmad; Dr. Rizwan Qaisar Danish; Syed Adnan Ali; Hafiz Fawad Ali; Dr. Asad Afzal Humayon (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- This study was aimed to throw light on the appraisal and reward system, and its effects on job satisfaction and employee performance in the banking sector of Pakistan. Design/Methodology- The research was based on primary data collected from the two major cities of Pakistan, Lahore and Kasur. A total of 250 structured questionnaires were rotated to Islamic and conventional banks in different parts of both cities. Out of these 222 questionnaires were returned and were in usable form. The data so collected was analyzed with the help of the Statistical Package for Social Sciences (SPSS). statistical techniques such as regression analysis, correlation analysis, descriptive analysis and t-test were used. Findings- The results of the study revealed that appraisal was negatively correlated while the reward system was positively correlated to employee performance. Practical implications- This research will help banks in reviewing their policies to make optimum use of their employees to meet certain goals of the bank. This research reveals that the appraisal system of the bank is affecting negatively on employees performance. This study will help in developing criteria which will help managers to appraise the employees in an effective way.